2020
DOI: 10.12688/f1000research.25073.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between neighbourhood cohesion and disability: findings from SWADES population-based survey, Kerala, India

Abstract: Background: The burden of disability on individuals and society is enormous in India, and informal care systems try to reduce this burden. This study investigated the association between neighbourhood cohesion and disability in a community-based population in Kerala, India. To the best of our knowledge, no previous studies have examined this association in India.   Methods: A cross-sectional household survey was conducted with 997 participants aged 30 years and above, in Kerala. Neighbourhood cohesion was asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Per capita income was an important predictor of self-reported disability. This is in line with a previous study where WHODAS 2.0 scores were higher for lowerincome participants 37 . Similar results were also found by Waterhouse et al (2017) 38 , which revealed that the poorest income quintile was associated with severe disability and the number of chronic diseases reported.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Per capita income was an important predictor of self-reported disability. This is in line with a previous study where WHODAS 2.0 scores were higher for lowerincome participants 37 . Similar results were also found by Waterhouse et al (2017) 38 , which revealed that the poorest income quintile was associated with severe disability and the number of chronic diseases reported.…”
Section: Discussionsupporting
confidence: 93%
“…Age was also a factor associated with disability, so that having fewer years of life decreased the disability score when the multivariate regression model was analyzed, although this difference was not signi cant (p>0.05) in the bivariate analysis of the general sample These results diverged in most studies that assessed disability in the elderly 29,37,38 . However, a possible explanation is that in the primary health care setting, older individuals with more severe di culties sought the units by spontaneous demand less than those individuals who were younger with the same degrees of perceived di culty, which could suggest a worse access for elderly people with higher levels of disability.…”
Section: Discussionmentioning
confidence: 85%
“…Second to family dependent networks, belonging to a locally integrated network, characterised by social cohesion has the potential to protect people from anxiety or depression. The components of social cohesion: trust, safety and participation [ 34 ] can modulate anxiety and depression in the people who share the collectivist value system [ 35 ]. Kerala State’s social welfare system has heavily invested in locally integrated networks, introducing a participatory bottom-up people’s planning approach [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Community cohesion is also an important protective factor for preventing posttraumatic stress disorder symptoms when older adults experience negative events and disasters [21]. Clinical and epidemiological studies have found a lack of community cohesion to be associated with disability, hypertension, myocardial infarction, stroke, and mortality [22][23][24][25]. Empirical studies have confirmed that low levels of community cohesion can accelerate epigenetic aging, and high levels of community cohesion can reduce the risks of diseases associated with genetic risk factors [26,27].…”
Section: The Importance Of Community Cohesionmentioning
confidence: 99%